2016
DOI: 10.1016/j.chest.2016.08.917
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Eosinophilic Pneumonia: Adjunctive Therapy With Inhaled Steroids

Abstract: a b s t r a c tIdiopathic chronic eosinophilic pneumonia (ICEP) is a rare form of diffuse parenchymal lung disease first identified by Carrington et al. in 1969. It is characterized by the presence of constitutional and respiratory symptoms with associated peripheral opacities on imaging and elevated serum and/or bronchoalveolar eosinophilia. Although data is limited regarding etiology or prevalence, it is known that ICEP has a 2:1 female: male predominance and typically affects non-smokers. Diagnosis rests on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The high recurrence rate of CEP can lead to steroid dependence, provoking research into other possible treatment options. One case report outlines a woman who maintained remission on inhaled steroids following systemic steroid cessation [ 11 ], but further research is necessary to conclude whether inhaled steroids may contribute to remission maintenance. There are few case reports that have reported that the anti-immunoglobulin E (anti-IgE) antibody omalizumab was used to treat cases of steroid-dependent eosinophilic pneumonia [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The high recurrence rate of CEP can lead to steroid dependence, provoking research into other possible treatment options. One case report outlines a woman who maintained remission on inhaled steroids following systemic steroid cessation [ 11 ], but further research is necessary to conclude whether inhaled steroids may contribute to remission maintenance. There are few case reports that have reported that the anti-immunoglobulin E (anti-IgE) antibody omalizumab was used to treat cases of steroid-dependent eosinophilic pneumonia [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Leukocytosis and peripheral eosinophilia are present in more than 90% of cases and may help signify an alternative diagnosis other than bacterial/viral pneumonia. There are no absolute diagnostic criteria for ICEP but diagnosis is made based on respiratory symptoms for at least 2 weeks, presence of multilobar peripheral ground‐glass opacities, and eosinophilia >40% on BAL or peripheral eosinophilia >1000/mm 3 in the absence of other eosinophilic lung diseases 1,3 . Other such causes of eosinophilic pneumonia that need to be excluded prior to diagnosis include but not limited to drug‐induced eosinophilic pneumonia, eosinophilic granulomatosis with polyangiitis (EGPA, also known as Churg Strauss), allergic bronchopulmonary aspergillosis (ABPA), and fungal and parasitic infections depending on exposure history 3 …”
Section: Discussionmentioning
confidence: 99%
“…Idiopathic chronic eosinophilic pneumonia, also known by the eponym Carrington disease, is a rare eosinophilic lung disease that accounts for less than 3% of cases of interstitial lung disorders 1 . Patients present with ill‐defined symptoms of dyspnea, cough, wheezing, and fatigue over several months as well as the presence of eosinophilia and opacities on chest imaging 2,3 . Once diagnosed, ICEP typically responds well to corticosteroid therapy.…”
Section: Introductionmentioning
confidence: 99%